Genetic mapping identifies genomic regions and candidate genes for seed weight and shelling percentage in groundnut - Gangurde, Sunil S.; Pasupuleti, Janila; Parmar, Sejal; Variath, Murali T.; Bomireddy, Deekshitha; Manohar, Surendra S.; Varshney, Rajeev K.; Singam, Prashant; Guo, Baozhu; Pandey, Manish K. (Frontiers in Genetics, 2023)
Seed size is not just a yield related trait but also an important measure to determine the commercial value of groundnut in international market. For instance, the small size is preferred in oil production, where and large size seed is preferred in confectioneries. In order to identify the genomic regions associated with 100 seed weight (HSW) and shelling percentage (SHP), the recombinant inbred line (RIL) population (Chico × ICGV 02251) with 352 individuals was phenotyped for three seasons and genotyped with Axiom_Arachis array containing 58K SNPs. A genetic map was constructed with 4199 SNP loci spanning a map distance of 2708.36 cM. QTL analysis identified five QTLs for SHP, with three consistent QTLs on chromosomes A05, B06 and B10. Similarly, for HSW, seven QTLs were identified located on chromosomes A01, A04, A10, B05, B06 and B09. BIG SEEDs locus and spermidine synthase candidate genes associated with seed weight were identified in the QTL region on chromosome B09. Laccase, fiber protein, lipid transfer protein, senescence-associated protein and disease resistant NBS-LRR proteins identified in the QTL regions associated with shelling percentage. Major effect QTLs for both traits successfully distinguished between the small and large seeded RILs. The QTLs identified for HSW and SHP can be used for development of potential selectable markers to improve the cultivars with desired seed size and shelling percentage to meet the demands of confectionary industries.